2021
DOI: 10.3991/ijim.v15i20.23715
|View full text |Cite
|
Sign up to set email alerts
|

Development and Expert Review of iZakat Kedah Mobile Application

Abstract: Zakat is a mandatory practice in Islam. The purpose of zakat is to help the society, share the endless boons of Allah and assists the unfortunate people to have a better quality of life. The concept of Zakat is to purify the Muslim wealth and soul. Calculation of Zakat is based on the total savings of a Muslim during one lunar (Islamic) year. Even though, paying Zakat is compulsory for all Muslims however, the knowledge of zakat and the calculation of zakat is still insufficiently explored by the Muslims thems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…There are a total of 5 experts involved in the evaluation phase to evaluate the Mobile AR4AsnafCare application prototype. The set of interview questions as suggested in Aziz et al, [26] and Omar et al, [27] is tabulated in Table 1 and the result is tabulated in Figure 8. Table 1 describes the list of six questions for expert that focus on design, content and function.…”
Section: Finding and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a total of 5 experts involved in the evaluation phase to evaluate the Mobile AR4AsnafCare application prototype. The set of interview questions as suggested in Aziz et al, [26] and Omar et al, [27] is tabulated in Table 1 and the result is tabulated in Figure 8. Table 1 describes the list of six questions for expert that focus on design, content and function.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Questions related to design, content, and functionality were prepared for the experts as suggested from Aziz et al, [26] and Omar et al, [27]. Then, the questions were given to the experts through Whatsapp during the online interview session.…”
Section: Methodsmentioning
confidence: 99%
“…The expert review technique was employed in the evaluation process, as suggested by authors in Ref. [19,20]. This study started with the literature analysis to identify the suitable therapeutic requirements to be adopted in the depression mobile application.…”
Section: Methodsmentioning
confidence: 99%
“…Both developed and emerging economies are severely affected by the unpredictable nature of oil prices. Due to several recent global economic catastrophes, investors are keen to learn how oil price fluctuations affect global financial markets, particularly stock market returns (Khan et al, 2021a;Ajmi et al, 2021;Omar et al, 2021). A nation's progress largely depends on the investment it receives in its economy.…”
Section: Introductionmentioning
confidence: 99%